Generalizability of glucagon‐like peptide‐1 receptor agonist cardiovascular outcome trials to the overall type 2 diabetes population in the United States. Issue 6 (12th March 2019) - Boye, Kristina S.; Riddle, Matthew C.; Gerstein, Hertzel C.; Mody, Reema; Garcia‐Perez, Luis‐Emilio; Karanikas, Chrisanthi A.; Lage, Maureen J.; Riesmeyer, Jeffrey S.; Lakshmanan, Mark C.
Abstract : Aim: To examine the generalizability of results from glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA) cardiovascular outcome trials (CVOTs) in the US type 2 diabetes (T2D) population. Materials and methods: Patients enrolled or eligible for inclusion in four CVOTs (EXSCEL, LEADER, REWIND, and SUSTAIN‐6) were examined in reference to a retrospective clinical database weighted to match the age and sex distribution of the US adult T2D population. We descriptively compared key baseline characteristics of the populations enrolled in each trial to those of the reference population and estimated the proportions of individuals in the reference population represented by those in the trials for each characteristic. We also estimated the proportions of individuals in the reference population that might have been enrolled in each trial based upon meeting the trial inclusion and exclusion (I/E) criteria. Results: No trial's enrolled population perfectly matched the reference population in key characteristics. The EXSCEL population most closely matched in mean age (62.7 vs. 60.5 years) and percentage with estimated glomerular filtration rate <60 (18.6 vs. 17.3%), while REWIND most closely matched in HbA1c, sex distribution, and proportion with a prior myocardial infarction. Based on I/E criteria, 42.6% of the reference population were eligible for enrolment in REWIND, versus 15.9% in EXSCEL, 13.0% in SUSTAIN‐6, and 12.9% in LEADER. Conclusions: Although none of the trials are fully representative of the general population, among the four trials examined, results from baseline REWIND were found to be more generalizable to the US adult T2D population than those of other GLP‐1 RA CVOTs.